Penatalaksanaan Fisioterapi pada Kasus Post Fraktur Calcaneus di RSUD Salatiga: Case Report - Muwahhidah Muwahhidah; Suryo Saputra Perdana; Reza Arshad Yanuar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction: A fracture is a discontinuity in bone (or cartilage) resulting from mechanical forces that exceed the bone's ability to support it. Objective: to determine physiotherapy management in cases of post left calcaneus fracture. Method: ultrasound therapy, stretching exercise, strengthening exercise. Results: evaluation of Manual Muscle Testing, Numeric Rating Scale, Foot and Ankle Disability (FADI) measurements during 4 meetings.